Load-Bearing Characteristics of Large-Diameter Rock-Socketed Piles Based on Ultimate Load Tests - Xueying Liu; Xiaoyu Bai; Mingyi Zhang; Yonghong Wang; Songkui Sang; Nan Yan (Advances in Materials Science and Engineering)
As part of a large converter project in Shandong Province, vertical static load tests and internal force tests were conducted on three large-diameter rock-socketed piles, their load transfer mechanism was clarified, and the ultimate side resistance and ultimate resistance performance characteristics of the rock-socketed sections were analyzed. The test results showed that the three test piles were damaged under maximum loading, the Q-s curve exhibited a steep drop, the pile compression was around 1.2 times the pile diameter, and the bearing capacity of a single pile did not meet the design requirements. The side and end resistances of the three test piles all reached their ultimate values, but the ultimate side resistance was lower than the lower limit of the recommended value in the current technical code for building pile foundations. The end resistance under maximum loading accounted for 38.4–53.8% of the peak load, which was relatively high. By comparing it with other studies, there was no significant correlation between the coefficient of rock ultimate side resistance of the rock-socketed segment and the pile diameter of the rock-socketed segment. However, the coefficient of ultimate resistance increased gradually with the pile diameter. However, the latter correlation was not significant when the pile diameter was less than 1000 mm.